Studi Kasus Pembebasan Tanah dalam Proyek Normalisasi Waduk Pluit Ditinjau dari Perspektif Hukum Agraria - Irawan, Iwan (Bina Nusantara University, 2014)
Construction always rises to polemics and conflicts of interest between landowners and the state guarantees the rights of ownership over the land. The government is trying to bridge the existing conflict of interest with the aim to achieve the infrastructure development by issuing regulations on land acquisition for public purposes. Conceptually, accommodation on the two interests has actually existed since 1960 when the Law of Principal Agrarian was formed. This paper aims to clarify that the provision of land for public purposes associated with the release/revocation of land rights and the rights of control by the state in Pluit Reservoir project normalization does not violate the Law and Human Rights. It is appropriate for the primary purpose of the Law of Pricipal Agrarian, which is for public interest and for the welfare of the whole society.